Clarifying the link between mastery goals and social comparisons in classroom settings - Chatzisarantis, Nikos; Nilay Ada, E.; Bing, Q.; Papaioannou, A.; Prpa, N.; Hagger, Martin (Academic Press, 2016)
Previous experimental studies have documented that competence evaluations are function of social comparison information pertaining to classmates' grades even among mastery-oriented students who are not supposed to base perceptions of competence on social comparisons. This study aimed to replicate this link between mastery goals and social comparisons by using a measure of achievement goals that captured the comparison standards that students intended to adopt in classroom settings. In addition, we examined whether mastery-oriented and performance-oriented students responded differently to social comparisons, particularly unfavourable social comparisons with more capable classmates. In a study that aimed to predict perceptions of competence among university students, we showed that mastery-oriented students who intended to adopt self-referenced standards of comparison based perceptions of competence on social comparisons. In addition, response surface analysis supported a "mastery goal advantage" effect whereby mastery goals yielded higher perceptions of competence than performance goals among students who engaged in unfavourable social comparisons. Findings suggest that mastery goals are adaptive not because they motivate students to not engage in social comparisons but because they lead students to respond to unfavourable social comparisons in an adaptive way.